THE ROLE OF CHARACTER EDUCATION IN IMPROVING STUDENTS LEARNING DISCIPLINE AT SDN 7 LINGE CENTRAL ACEH - siti Rosnawati; Siti Mayang Sari; Fitriani Manurung; Sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Character education and learning discipline are integral aspects in thecontext of basic education, having an important role in shaping the characterand quality of students. Both are not just elements of formal education, but formthe foundation for the formation of individuals with integrity and character.Character education and learning discipline complement each other, creating aholistic learning environment that has a positive impact on the development ofstudents in the increasingly complex era of modern education. This researchaims to describe the role of character education in improving students' learningdiscipline. This research uses descriptive qualitative methods. Based on theresults of research that has been conducted, SDN 7 Linge applies acomprehensive approach in integrating character education into the curriculum.This approach involves character values as an integral part of education, notjust as a separate lesson. Character education at SDN 7 Linge shows thatcharacter development is not a separate goal from formal education, but is aninseparable part. By creating a learning environment that supports charactervalues, this school aims to form students who are academically intelligent andhave strong character, are ethical and responsible in society.